THE FUNCTION OF ACTIVITIES IN ENHANCING SPEAKING ABILITY - Ochilova Nasiba Sotqinovna (Scholar Express Journal, 2025)
This article talks about formation of communication culture of students in a foreign language based on various techniques. These are developed on the basis of discussion, reading, the information gap activities.
Keywords: speaking; discussion; reading